The impact of artificial intelligence systems on business performance - Rizaeva Farangiz Kholdorovna (Zien Journals, 2022)
This article examines the impact of artificial intelligence on enterprises and the expected efficiency from it, and analyzes the impact of artificial intelligence on the economy using a neoSchumpeterian economic approach. Artificial intelligence systems
Keywords: artificial intelligence; Schumpeter's economics; digitization; SI applications